Reassessing the Export Proceeds Retention Policy and Its Impact on Corporate Liquidity: Evidence from Indonesia’s Coal Sector - Raymond Erlangga Siringoringo; Diani Sadiawati (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
This study addresses the microeconomic vulnerabilities of capital-intensive sectors subjected to macro-monetary state interventions. While prior research predominantly evaluates natural resource export proceeds (Devisa Hasil Ekspor Sumber Daya Alam / DHE SDA) through a macro-monetary lens, a critical analytical gap persists regarding the impact of aggressive foreign-exchange retentions on corporate financial viability. Employing a convergent parallel mixed doctrinal-normative and empirical single-case study of the Indonesian coal mining sector under Peraturan Pemerintah Nomor 8 Tahun 2025, this paper examines compounding regulatory burdens and systemic legal antinomies. Normative findings reveal a severe validity flaw, as the 100% retention mandate violates the statutory foreign exchange freedoms guaranteed under Undang-Undang Nomor 24 Tahun 1999. Empirically, simulations demonstrate that freezing export proceeds for 12 months creates chronic cash flow mismatches, forcing corporations into high-cost commercial refinancing that erodes net profit margins by 9% to 27% and causes severe market asymmetries favoring large-scale conglomerates over vulnerable mid- to low-tier enterprises. Theoretically, this study bridges the economic law and corporate governance literature by conceptualizing a unique "compounding regulatory burden" framework. In practice, it offers actionable policy reforms for adaptive, conditional, and downstream-linked foreign exchange models to preserve private-sector survival without compromising sovereign monetary defense.